WTO: NATIONAL TREATMENT AND THE LAW OF UZBEKISTAN - Fayzullayeva Shahlo Jumaniyoz qizi (Web of Journals Publishing, 2023)
This article explores the critical concept of "national treatment" within the framework of the World Trade Organization (WTO) and its implications for the legal landscape of Uzbekistan. As a (potential) WTO member, Uzbekistan is bound by the principle of national treatment, which mandates that foreign goods and services must receive the same treatment as domestic ones. This article delves into the impact of national treatment on Uzbekistan's legal system, analyzing how the country's domestic laws and regulations align with this WTO principle. By examining specific cases and regulations, the article sheds light on the challenges and opportunities that arise in the context of Uzbekistan's international trade commitments.
Keywords: WTO; National Treatment; Uzbekistan; International Trade Law; Domestic Regulations.